PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT RAI GETHEG KREATIF BEKASI - Kusuma, Wisnu; Sari, Rycha Kuwara; Puspitorini, Ferawaty (SINERGI : Jurnal Riset Ilmiah, 2025)
The influence of workload and work environment on employee performance at PT Rai Getheg Kreatif Bekasi. The method used was a quantitative approach with a multiple linear regression design, where data were collected through questionnaires distributed to 50 employees. The theory underlying this study encompasses the concepts of workload, work environment, and employee performance, which are interrelated in influencing individual productivity within an organization. The results of the analysis indicate that both workload and work environment have a positive and significant effect on employee performance, with a coefficient of determination (R²) of 68.5%, meaning that 68.5% of the variation in performance can be explained by these two variables. The implication of this study is the importance of balanced workload management and the creation of a conducive work environment, so that companies can sustainably increase employee productivity and performance effectiveness.